Media Sosial dan Revolusi Politik: Memahami Kembali Fenomena âArab Springâ dalam Perspektif Ruang Publik Transnasional - Umar, Ahmad Rizky Mardhatillah; Darmawan, Arief Bakhtiar; Sufa, Faela; Ndadari, Gebyar Lintang (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This paper aims to analyze some linkages between revolution, public sphere, and transnational activism through social media in the Middle East. A revolution in Tunisia in 2011 became an international issue after the revolution spreaded to other states in the region. After Tunisia, protest movements began to ignite in Egypt, Libya, Yemen, and Jordania. This wave of revolution comes into a public discourse: what causes this movement? How could a revolution in one country inspire another revolution in another country? To answer these questions, we analyze the role of social media as a âbridgeâ to connect activists in the Middle East to make a revolution. We conclude that transnational activism was formed by routine and massive reports from media which explained what hadhappened in the Middle East during the revolution. The reports were followed by a spread of the idea of democracy and civil rights through social media. As a consequence, revolution took place in several other countries whose socio-cultural tradition are similar to that of Tunisia.